If $x$,$y$,$z$ are positive real numbers,Prove:$$\sum \limits_{cyc} \frac{x}{x+\sqrt{(x+y)(x+z)}}\leq 1$$ Using this two inequality:

$\sum ^n_{i=1} \sqrt{a_ib_i}\leq\sqrt {ab} $ (we call it $A$ inequality)

$\frac {ab}{a+b} \geq \sum ^n_{i=1} \frac{a_ib_i}{a_i+b_i}$ (we call it $B$ inequality)

which $a_i$ and $b_i$ are positive and and $b= \sum ^n_{i=1} b_i$,$a= \sum ^n_{i=1} a_i$.

Additional info: The question emphasizes in using inequalities $A$ and $B$.Beside them we can use AM-GM and Cauchy inequalities only.We are not allowed to use induction.And if you like,here you can see Prove of inequality B.

Things I have tried so far:

Using inequality $A$ i can re write question inequality as$$\sum \limits_{cyc} \frac{x}{2x+\sqrt{xy}}\leq 1$$

And I can't go further.I can't observer something that could lead me to using inequality $B$.


Use the fact $\sqrt{(x+y)(x+z)}\ge \sqrt{xy}+\sqrt{xz}$. Which is obvious after squaring and cancelling terms. Now our inequality becomes : $$\sum \limits_{cyc} \frac{x}{x+\sqrt{(x+y)(x+z)}}\le \sum \limits_{cyc} \frac{x}{x+\sqrt{xy}+\sqrt{xz}}=\sum \limits_{cyc} \dfrac{\sqrt{x}}{\sqrt{x}+\sqrt{y}+\sqrt{z}}=1$$

| cite | improve this answer | |
  • $\begingroup$ thanks for hint,i'm trying figuring out the part you write $\sum \frac{x}{x+\sqrt{xy}+\sqrt{xz}}=1$.can you give me a hint on how you concluded that? $\endgroup$ – user2838619 Jul 30 '14 at 14:40
  • $\begingroup$ That was not a hint actually, its the full solution lol. Anyhoo I am editing it so you get a clearer idea. $\endgroup$ – shadow10 Jul 30 '14 at 15:10
  • $\begingroup$ How i missed a simple factoring like that.thanks. $\endgroup$ – user2838619 Jul 30 '14 at 15:19
  • $\begingroup$ So only inequality A is needed. $\endgroup$ – Ewan Delanoy Jul 30 '14 at 15:19
  • 2
    $\begingroup$ funny thing is Mathematica has serious problem with it $\endgroup$ – user2838619 Jul 30 '14 at 16:19

By your work and by C-S we obtain: $$\sum_{cyc}\frac{x}{x+\sqrt{(x+y)(x+z)}}\leq\sum_{cyc}\frac{x}{2x+\sqrt{yz}}=\frac{3}{2}-\sum_{cyc}\left(\frac{1}{2}-\frac{x}{2x+\sqrt{yz}}\right)=$$ $$=\frac{3}{2}-\frac{1}{2}\sum_{cyc}\frac{\sqrt{yz}}{2x+\sqrt{yz}}=\frac{3}{2}-\frac{1}{2}\sum_{cyc}\frac{yz}{2x\sqrt{yz}+yz}\leq$$ $$\leq\frac{3}{2}-\frac{1}{2}\cdot\frac{\left(\sum\limits_{cyc}\sqrt{yz}\right)^2}{\sum\limits_{cyc}(2x\sqrt{yz}+yz)}=\frac{3}{2}-\frac{1}{2}=1.$$

| cite | improve this answer | |

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.